Keamanan Data Transaksi Nasabah Pada Aplikasi Bank Sampah Berbasis Web Menggunakan Algoritma AES - Aditya Puji Nugroho; Arini Arini; Hendra Bayu Suseno (Query: Journal of Information Systems, 2020)
The Malacca waste bank located in East Jakarta was established in 2008, the Malacca waste bank has a number of customers reaching more than 300 people and the waste absorbed every month reaches 2 - 2.5 tons. In carrying out its activities, the Malacca Sari waste bank still has several problems, including: the difficulty of recording the income of waste, the lack of integrity between the customer's savings book and the garbage bank's bookkeeping and the customer often does not carry a savings book, and even something is missing, to anticipate this and improve the services of the garbage bank, we need an application for processing data effectively and efficiently, which can have a secure data storage system and complement the application with good security techniques. In this case the researcher uses the cryptographic algorithm (Advanced Encryption System). With this application, it is expected that transaction data information stored in the application will be safe and not known to eavesdroppers or irresponsible parties. In this application, the encrypted information is only in the form of balance data at a garbage bank and only the management and customers can use this application. Based on program implementation and testing, researchers can conclude that this application is easy to use, the confidentiality of data and information able to maintain and protect Keywords : AES (Advanced Encryption System), MySQL, Cryptographic, Php, Waste Bank.